2011
DOI: 10.1590/s0104-14282011005000032
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de diferentes amostras de mandioca por espectroscopia de ressonância magnética nuclear

Abstract: Resumo: A raiz de mandioca (Manihot esculenta crantz) é cultivada nas mais diversas regiões do Brasil e desempenha importante papel na dieta alimentar dos brasileiros, representando para muitas famílias do Norte e Nordeste a principal fonte energética. A farinha de mandioca constitui-se num alimento com alto teor de amido, além de conter fibras, lipídeos e alguns minerais, entretanto apresenta grande variabilidade genética, o que resulta em diferenciação na sua constituição química e estrutural. Frente à impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[55][56][57][58] The glycolipids class have shown the corresponding peaks 1-8 in addition to the characteristic peaks of the classes, such as the peaks 14-19. 59,61 As for the phospholipids, the common peaks were 1-5, 8 and 10 plus the specific peaks 20-23 ( Figure S3, SI section). 56 The spectral information obtained from the fractions of lipids was important for confirmation of interpretation of total lipids spectra.…”
Section: Lipid Analysis Using 1 H Nmrmentioning
confidence: 97%
“…[55][56][57][58] The glycolipids class have shown the corresponding peaks 1-8 in addition to the characteristic peaks of the classes, such as the peaks 14-19. 59,61 As for the phospholipids, the common peaks were 1-5, 8 and 10 plus the specific peaks 20-23 ( Figure S3, SI section). 56 The spectral information obtained from the fractions of lipids was important for confirmation of interpretation of total lipids spectra.…”
Section: Lipid Analysis Using 1 H Nmrmentioning
confidence: 97%
“…C1 is on the side corresponding to the lower energy field, while C6 is on the higherenergy-field side [62]. C2, C3, and C5 fall between these extremes, and their signals were associated with spectra at approximately 72 ppm and attributed to the HC-O groups [63]. Smits et al [64] observed the interaction between starch and plasticizer in the 13 C NMR spectra.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…Samples were placed into NMR tubes five mm in diameter and subsequently in a five mm probe. Typical acquisition parameters included frequency of observation of 200.0 MHz, acquisition time 4.0 s, spectral 3200.0 Hz window, pulse width 0.0 µs, number of accumulations (410), interval between pulses 1.0 s. The spectra were processed by MestReNova® program version 6.1.0 and the chemical shifts are expressed in ppm (Iulianelli and Tavares, 2011;Prestes et al, 2012).…”
Section: H Nmr Spectramentioning
confidence: 99%
“…So the high-resolution NMR technique, such as 1 H, is a viable alternative in the study of organic compounds due to the simplicity and the importance of information generated (Iulianelli and Tavares, 2011).…”
mentioning
confidence: 99%